Assessing Specialized Metabolite Diversity in the Cosmopolitan Plant Genus Euphorbia L. - Ernst, Madeleine; Nothias, Louis-Félix; van der Hooft, Justin J. J.; Silva, Ricardo R.; Saslis-Lagoudakis, C. Haris; Grace, Olwen M.; Martinez-Swatson, Karen; Hassemer, Gustavo; Funez, Luís A.; Simonsen, Henrik T.; Medema, Marnix H.; Staerk, Dan; et al. (Frontiers in Plant Science, 2019)
Coevolutionary theory suggests that an arms race between plants and herbivores yields increased plant specialized metabolite diversity and the geographic mosaic theory of coevolution predicts that coevolutionary interactions vary across geographic scales. Consequently, plant specialized metabolite diversity is expected to be highest in coevolutionary hotspots, geographic regions, which exhibit strong reciprocal selection on the interacting species. Despite being well established theoretical frameworks, technical limitations have precluded rigorous hypothesis testing. Here we aim at understanding how geographic separation over evolutionary time may have impacted chemical differentiation in the cosmopolitan plant genus Euphorbia. We use a combination of state-of-the-art computational mass spectral metabolomics tools together with cell-based high-throughput immunomodulatory testing. Our results show significant differences in specialized metabolite diversity across geographically separated phylogenetic clades. Chemical structural diversity of the highly toxic Euphorbia diterpenoids is significantly reduced in species native to the Americas, compared to Afro-Eurasia. The localization of these compounds to young stems and roots, suggest a possible ecological relevance in herbivory defense. This is further supported by reduced immunomodulatory activity in the American subclade as well as herbivore distribution patterns. We conclude that computational mass spectrometric metabolomics coupled with relevant ecological data provide a strong tool for exploring plant specialized metabolite diversity in a chemo-evolutionary framework.